Women Entrepreneurship in Bhaktapur Durabar Square: An Investigation on Status, Problems and Prospects - Pokharel, Prakash (KMC Research Journal, 2024)
Women entrepreneurs can contribute significantly to economic development in Nepal but their contribution has not been adequately studied and developed. Although it is challenging for both men and women to start and sustain a successful business, women face unique challenges to self-employment. The objective of Field Surveywas to explore nature of women entrepreneurs, to investigate background and motivational factor, to identify the challenges of women entrepreneurs business in Bhaktapur Durbar Square area and to make practical recommendations to enhance women entrepreneurship. A survey that included 52 women-owned businesses was conducted. Women entrepreneurs in Field Surveywere motivated by pull factors, such as the need for extra income, empowerment and social recognition. They are currently facing obstacles, such as high interest, lack of business management skill, pressure of childcare, lack of self confidence and socio-culture environment (dual responsibility, restrictions on mobility). They furthermore, indicated financial support, business training and advice, the need to network with other business owners and marketing support as their main support needs. Practical recommendations are suggested to stakeholders and women entrepreneurs to overcome these obstacles and to ensure that women entrepreneurs can sufficiently contribute to the economy and empower themselves economically.